2013
DOI: 10.1002/jcp.24431
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16E (GDD1) Exhibits Protein Instability and Distinct Characteristics in Chloride Channel/Pore Forming Ability

Abstract: TMEM16E/GDD1 has been shown to be responsible for the bone-related late-onset disease gnathodiaphyseal dysplasia (GDD), with the dominant allele (TMEM16E(gdd) ) encoding a missense mutation at Cys356. Additionally, several recessive loss-of-function alleles of TMEM16E also cause late-onset limb girdle muscular dystrophy. In this study, we found that TMEM16E was rapidly degraded via the proteasome pathway, which was rescued by inhibition of the PI3K pathway and by the chemical chaperone, sodium butyrate. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Consistent with previous studies , our data also show that recombinant Ano5 resides primarily on the ER membrane and intracellular vesicles (Figure ). To study the expression and subcellular localization of endogenous Ano5 in human muscles, we performed immunofluorescence staining with the N421A/85 antibody and the antibody against dystrophin or calnexin.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies , our data also show that recombinant Ano5 resides primarily on the ER membrane and intracellular vesicles (Figure ). To study the expression and subcellular localization of endogenous Ano5 in human muscles, we performed immunofluorescence staining with the N421A/85 antibody and the antibody against dystrophin or calnexin.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies showed that Ano5 was rapidly degraded via the proteasome pathway and transient transfection with a plasmid encoding Ano5‐GFP resulted in very low GFP fluorescence , despite the high transfection efficiency. To validate the antibodies raised against human/mouse Ano5 antigens, we constructed a recombinant adenovirus (Ad) expressing human Ano5 with FLAG and YFP tags at the N‐ and C‐terminus, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this possibility, it would be necessary to determine whether the TMEM16A-E SCRD chimera can support microparticle production. Point mutations found in GDD patients appear to make the TMEM16E dominant-active (11,59). It will be interesting to examine the structure of intracellular membranes in cells expressing these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM16E, which was not found to produce CaCC [32]. Instability of TMEM16E may be the cause for gnathodiaphyseal dysplasia [32,33].…”
Section: Camentioning
confidence: 85%
“…Instability of TMEM16E may be the cause for gnathodiaphyseal dysplasia [32,33]. Although ANO5 is expressed primarily in muscle, bone, and testis, other studies also suggest expression in the gastrointestinal tract and in lung [19,34].…”
Section: Camentioning
confidence: 94%